OS12.2 Targeting epigenetic pathways in the treatment of recurrent high-grade glioma. (6th September 2019) - Hau, A; Houben, L; Klein, E; Oudin, A; Stieber, D; Flies, B; Kaoma, T; Azuaje, F; Fritah, S; Bjerkvig, R; Hertel, F; Mittelbronn, M; et al.
Abstract: BACKGROUND: High grade glioma (HGG) patients develop resistance to standard treatment leading to disease progression and limited life expectancy. Advances in the molecular characterisation of treatment-naïve HGGs based on next-generation sequencing and DNA methylation analyses have led to a better delineation of HGG subtypes and the identification of distinct genomic abnormalities. Furthermore, using large patient cohorts of longitudinal tumor samples, comprehensive genomic profiling studies emerged to investigate therapy-associated evolution of gliomas. All together, those studies point out the need for personalised treatment strategies, where applied drugs will be adapted to the unique patient-specific genetic abnormalities. MATERIAL AND METHODS: We collected fresh samples of more than 800 brain tumors containing almost 300 glioma specimen with approximately 100 longitudinal samples of initial and recurrent tumors from 43 matched patients. By now, we have successfully established 34 patient-derived orthotopic xenografts (PDOXs) in mice. We performed comprehensive molecular profiling using array comparative genomic hybridisation, DNA methylation analysis and targeted DNA sequencing on patient specimen and their derivatives such as 3D tumor organoids and PDOXs. The custom-design sequencing panel comprises 234 genes that reflect both established genetic identifiers for individual glioma subtype classification and novel genes encoding mainly epigenetic effector genes. Based on patient-derived material we carried out drug response screening on 3D tumor organoids using a compound library matching the majority of genes that were assessed by targeted sequencing. RESULTS: We succeeded in generating a live biobank of HGG patient-derived xenografts and 3D organoids that neatly recapitulates the mutational spectrum including structural DNA variation and methylation-based subtypes of gliomas. A highlight is the generation of 19 PDOXs of paired initial and relapse HGGs from a total of 9 glioma patients. A detailed analysis of the paired longitudinal samples indicated that PDOX models closely recapitulate the evolutionary trajectory of the parental tumors. Targeted sequencing of longitudinal HGG PDOXs suggests that relapse tumors accumulate somatic mutations in epigenetic effectors compared with the Initial. Differential drug responses between initial and relapse tumors were observed after screening of in vitro 3D tumor organoids. CONCLUSION: Response assessment of naïve initial gliomas and recurrences provides crucial information on the differential sensitivity between initial and relapsed HGGs and offers novel personalised therapeutic options in the relapse setting. Furthermore, in depth correlation of the profiled somatic molecular landscape with drug response will enable pharmacogenomic predictions of potential inhibitors in the clinical setting.